The Influence of Transformational Leadership, Digital Competence, and Self-Efficacy on Teacher Performance in the Society 5.0 Era - Rohimah Nur Nasution; Hariman Syaleh (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
The transition toward Society 5.0 has transformed the educational landscape by requiring teachers to integrate digital technology into learning while maintaining a human-centered approach. However, preliminary observations at SMK Paramitha Bukittinggi revealed that many teachers still experienced difficulties in using digital technologies effectively, indicating challenges related to leadership support, digital competence, and self-efficacy. This study aims to analyze the influence of transformational leadership, digital competence, and self-efficacy on teacher performance in the Society 5.0 era. The research employed a quantitative approach with a causal associative design. The population consisted of all 35 teachers at SMK Paramitha Bukittinggi, and total sampling was applied so that the entire population served as research respondents. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with the Ordinary Least Squares (OLS) method through SPSS version 25. The findings revealed that transformational leadership had a positive and significant effect on teacher performance (t = 2.407; p = 0.016), digital competence also had a positive and significant effect (t = 2.277; p = 0.027), and self-efficacy showed the strongest positive and significant effect (t = 15.658; p = 0.000). Simultaneously, the three independent variables significantly influenced teacher performance (F = 378.268; p = 0.000), with an adjusted R² value of 0.859, indicating that 85.9% of the variation in teacher performance could be explained by the model. The study concludes that transformational leadership, digital competence, and self-efficacy are critical determinants of teacher performance in the Society 5.0 era. Strengthening these factors can significantly enhance teachers' ability to adapt to technological advances and improve the quality of learning processes.